2012
DOI: 10.1139/h2012-089
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium citrate supplementation enhances rehydration and recovery from rapid body mass loss in trained wrestlers

Abstract: This study assessed the effects of dietary sodium citrate supplementation during a 16 h recovery from 5% rapid body mass loss (RBML) on physiological functions, affective state, and performance in trained wrestlers. Sixteen wrestlers performed an upper body intermittent sprint performance (UBISP) test under three conditions: before RBML, after RBML, and after a 16 h recovery from RBML. During recovery, the subjects ate a prescribed diet supplemented with sodium citrate (600 mg·kg(-1); CIT group, N = 8) or plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…An upper-body intermittent sprint performance (UBISP) test developed by Hickner et al (1991) has been shown to produce similar high blood lactate concentration as an actual competitive wrestling match (Aedma et al 2013;Aschenbach et al 2000;García-Pallarés et al 2011;Hüb-ner-Wozniak et al 2006;Timpmann et al 2012;Walberg Rankin et al 1996) and the wrestlers tested have confirmed receiving a wrestling-like fatigue feeling post-test (Hickner et al 1991). Furthermore, upper-body anaerobic peak power (PP) and mean power (MP) attained in highintensity arm-cranking exercise are considered important success factors for wrestling (García-Pallarés et al 2011;Hübner-Wozniak et al 2006).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…An upper-body intermittent sprint performance (UBISP) test developed by Hickner et al (1991) has been shown to produce similar high blood lactate concentration as an actual competitive wrestling match (Aedma et al 2013;Aschenbach et al 2000;García-Pallarés et al 2011;Hüb-ner-Wozniak et al 2006;Timpmann et al 2012;Walberg Rankin et al 1996) and the wrestlers tested have confirmed receiving a wrestling-like fatigue feeling post-test (Hickner et al 1991). Furthermore, upper-body anaerobic peak power (PP) and mean power (MP) attained in highintensity arm-cranking exercise are considered important success factors for wrestling (García-Pallarés et al 2011;Hübner-Wozniak et al 2006).…”
mentioning
confidence: 99%
“…Sodium bicarbonate successfully induced metabolic alkalosis but no ergogenic effect from ingestion of either supplement was observed. Timpmann et al (2012) reported that dietary sodium citrate supplementation compared to placebo increased blood buffering capacity and plasma volume and stimulated regain of body mass through increased water retention during 16 h recovery after rapid body mass loss in trained wrestlers. However, sodium citrate did not increase PP or MP attained in UBISP test.…”
mentioning
confidence: 99%
See 3 more Smart Citations